PENETAPAN KADAR FORMALDEHID DALAM IKAN ASIN DI TULUNGAGUNG MENGGUNAKAN METODE SPEKTROFOTOMETRI VISIBLE - Muadifah, Afidatul; Djatmika, Rosalina; Ariani, Fahima (Jurnal SainHealth, 2019)
Formaldehyde steam stimulates the mucous membranes of the nose, throat and burning sensation. The use of formaldehyde as a preservative in food still occurring to date, one of which is the use of formaldehyde in salted fish consumed by community. The purpose of this study was todeterminetheoptimum condition of visible spectrophotometry methodand to know the concentration offormaldehyde contained insalted fish sold at Tulungagungwhich wasanalyzed using visible spectrophotometry method.The method used in this research is wavelength and solvent optimazation. Validation used is linearity, accuracy and precision. The identification of formaldehyde of salted fish was qualitatively identified using the peelof dragon fruit and KMnO4and quantitative using visible spectrophotometry method.Theresult of the research obtainedoptimumwavelengthis 530 nm, the optimum solvent is aquades. Result of linearity test obtained y = 0.003x + 0.489 with R2= 0.989. The accuracy test obtained recovery of 101.90% and precision test obtained SD = 1.583 and RSD = 1.95%. Qualitative test was obtained from 6 salted fish samples analyzed, all samples positive contain formaldehyde. In a quantitative analysis obtained formaldehyde of 72± 1,583 ppm.